Respuesta :

Option A:

[tex]g(f(x))=4x^4+4x^2[/tex]

Solution:

A composite function is created when one function is substituted into another function.

Given [tex]f(x)=2 x^{2}[/tex] and [tex]g(x)=x^{2}+2 x[/tex]

To find which expression represents [tex]g(f(x))[/tex].

Substitute f(x) into the function g(x).

[tex]g(f(x))=g(2x^2)[/tex]

Here [tex]2x^2[/tex] in place of x. So expand it using [tex]g(x)=x^{2}+2 x[/tex].

          [tex]=(2x^2)^2+2(2x^2)[/tex]

          [tex]=2^2x^4+4x^2[/tex]

          [tex]=4x^4+4x^2[/tex]

[tex]g(f(x))=4x^4+4x^2[/tex]

Option B is the correct answer.

Hence [tex]g(f(x))=4x^4+4x^2[/tex].